Internal Control System For Cash Purchases of Merchandise at ArfapuriMart - Aurellia, Nafizha Rahma; Ramadhan, Hibatullah Akmal; Aini, Devi Ayunda Nur; Pasetiya, Andrean Dwi; Ahmada, Kaiv Isa; Atho’ Urrohman, Wildan (PT Global Digital Sains Tekno, 2025)
Purpose: This study aims to examine the cash purchase procedures at ArfapuriMart, a small retail business in Indonesia, and assess how effectively internal control elements are implemented. It also seeks to uncover weaknesses arising from the absence of formal documentation and the centralization of authority. Method: A qualitative approach using a case study method was applied. Data were gathered through interviews with staff and management, supported by document reviews. The evaluation was conducted using internal control theories from Mulyadi and other accounting information systems literature to assess the effectiveness of internal controls in practice. Findings: The analysis indicates that although both manual and electronic processes are used in purchasing, critical control elements are lacking. Key documents like purchase requisitions and goods receipt forms are not in use. The purchasing authority is centralized in the owner’s hands, and roles are not clearly separated, increasing the risk of error or fraud. The digital system in place aids transaction recording and inventory tracking but lacks features like access restrictions and activity monitoring, limiting its reliability and transparency. Implication: These findings emphasize the importance for MSMEs to introduce structured documentation, formal procedures, and clear role distribution. Doing so will improve internal control, reduce risks, and support more accountable and efficient operations. Originality: This research adds unique insights into the internal control challenges faced by informal small businesses in Indonesia. It provides applicable recommendations for MSMEs aiming to strengthen their purchasing systems and internal governance structures.